PENERAPAN MODEL PEMBELAJARAN MULTIMEDIA DRILL AND PRACTICE UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS PADA MATA PELAJARAN MATEMATIKA SISWA KELAS III SD N 3 BRAJA HARJOSARI - Eris Septiana; KMA Fauzi; Andayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to implement a multimedia-based Drill and Practice learning model to improve the critical thinking abilities of third-grade students in mathematics at SD Negeri 3 Braja Harjosari. The problem identified in the classroom was the low development of students’ critical thinking skills, which was addressed by integrating an interactive and technology-supported learning approach. The implementation was conducted over three sessions using a mathematics learning application designed for structured practice, accompanied by teacher explanation, independent exercises, and feedback discussions. The study employed pretest–posttest design, including N-Gain and paired sample t-test analyses. The results show significant improvements in students’ performance, with average posttest scores increasing from 65–70 to 85–95. The N-Gain score of 0.681 indicates a medium-to-high level of improvement, while the paired sample t-test revealed a significant difference between pretest and posttest scores (p < 0.05). The multimedia Drill and Practice model effectively strengthened students’ conceptual understanding, analytical skills, and motivation through repetitive exercises, immediate feedback, and engaging visualizations. Challenges such as technical difficulties and test anxiety were resolved through additional guidance and more flexible assessment approaches. The findings suggest that the multimedia Drill and Practice model is a beneficial instructional strategy for enhancing critical thinking in elementary mathematics learning and is recommended for broader application with further integration of active learning and project-based activities.